Solid-state lithium-sulfur battery adopting sulfurized polyacrylonitrile positive electrode and self-healing polymer electrolyte and preparation method of solid-state lithium-sulfur battery
By using vulcanized polyacrylonitrile positive electrode and self-healing polymer electrolyte in lithium sulfur batteries, the problems of poor safety and circulation stability of lithium sulfur batteries are solved, and a solid lithium sulfur battery with high energy density, stable circulation performance and high safety are achieved.
Patent Information
- Application Number
- CN202411862371.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-18
AI Technical Summary
Lithium-sulfur batteries have problems with poor safety and circulation stability, especially due to the side reaction between lithium metal and electrolyte, the battery curloss efficiency and damage to safety.
A solid lithium-sulfur battery was obtained by in-situ polymerization using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte. Self-healing polymer electrolytes have high ionic conductivity, good interface contact and self-healing ability, improving the cycling stability and rate performance of the battery.
The stable cycle performance and high safety of solid-state lithium-sulfur batteries are achieved, while improving the energy density and capacity retention rate of the battery.
Smart Images

Figure CN119650871A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid-state lithium-sulfur batteries, and relates to a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte and a preparation method thereof. Background Art
[0002] Rechargeable lithium-sulfur batteries have a high theoretical energy density (2500Wh kg -1 ) has been considered as a more attractive next-generation energy storage battery than lithium-ion batteries. In 2009, Linda F. Nazar's research group first used mesoporous carbon (CMK-3) and sublimated sulfur to synthesize a reversible capacity of up to 1320 mA hg -1 Sulfur-containing cathode materials. However, due to the insulating properties of sulfur and Li2S, traditional carbon / sulfur composite cathodes usually exhibit poor electrochemical activity. In addition, the system adopts a solid-liquid-solid reaction pathway, which has a serious polysulfide shuttle effect, resulting in a rapid decrease in the coulombic efficiency of the battery and contamination of the electrolyte.
[0003] In order to improve the above problems, Professor Wang Jiulin's research group reported for the first time a sulfurized polyacrylonitrile material. Unlike carbon / sulfur composites, the sulfur-based active substances in sulfurized polyacrylonitrile are covalently bonded to the nitrogen-containing conductive framework, which has obvious electrochemical advantages. First, the strong bond with the framework can better prevent sulfur dissolution and side reactions with the electrolyte. This bond can achieve and maintain the molecular / atomic dispersion of sulfur and improve the full electrochemical activity of sulfurized polyacrylonitrile. By tightly connecting short sulfur chains (S2-S4) to the carbon backbone of a special polymer through chemical bonds, a direct conversion between low-order lithium polysulfides (Li2Sx, x≤4) and solid-phase Li2S is achieved. Therefore, lithium-sulfur batteries using the solid-solid conversion mechanism of sulfurized polyacrylonitrile effectively solve the traditional shuttle problem. At present, the main defects of sulfurized polyacrylonitrile positive electrode materials are their slow electrochemical reaction kinetics and poor electrochemical performance at high active material loadings.
[0004] On the other hand, lithium metal is used as the negative electrode in lithium-sulfur batteries. The active lithium metal is easy to react with commercial ether-based electrolytes, producing a large amount of "dead lithium" at the electrode / electrolyte interface, which has a negative impact on the safety and cycle stability of the battery. This conflicts with the realization of high energy density and high safety of lithium-sulfur batteries.
[0005] Gel polymer electrolyte is a liquid electrolyte wrapped by a small amount of polymer network, and its ionic conductivity and phase properties are between those of liquid electrolytes and solid electrolytes. Combining the advantages of liquid electrolytes and solid polymer electrolytes, it has attracted more and more attention. In addition, due to the strong processability of polymers, gel polymer electrolytes can also be used in wearable devices and flexible electronic devices, greatly expanding the scope of use of lithium-ion batteries. At present, the large-scale application of gel polymer electrolytes is mainly limited by the poor interface contact between electrodes and electrolytes and the low ionic conductivity. Summary of the invention
[0006] In view of the technical problems of poor safety and cycle stability of lithium-sulfur batteries in the prior art, the purpose of the present invention is to provide a solid-state lithium-sulfur battery and a preparation method using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, firstly by treating the polyacrylonitrile to reduce the manufacturing cost of the positive electrode material, and then obtain a solid-state lithium-sulfur battery by in-situ polymerization. The self-healing polymer electrolyte has high ionic conductivity, good flexibility, and good interface contact. When applied to lithium-sulfur batteries, the solid-state lithium-sulfur batteries can have stable cycle stability and rate performance.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte comprises the following steps:
[0009] The polyacrylonitrile is subjected to sand milling and then granulated by spray drying to obtain porous polyacrylonitrile particles;
[0010] The porous polyacrylonitrile particles, sublimated sulfur and a catalyst are ball-milled to obtain a powder, and the powder is subjected to a first heat treatment and then to a second heat treatment to obtain a sulfurized polyacrylonitrile positive electrode powder;
[0011] The polyacrylonitrile sulfide positive electrode powder, conductive carbon black and binder are mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried to obtain the polyacrylonitrile sulfide electrode sheet;
[0012] Adding lithium salt to a mixed solution of ethylene carbonate, dimethyl carbonate and fluoroethylene carbonate, stirring, to obtain a basic electrolyte precursor;
[0013] Adding polymer monomers, self-healing functional monomers, ionic liquids and thermal initiators to a basic electrolyte precursor, stirring, and obtaining a self-healing polymer electrolyte precursor solution;
[0014] The sulfide polyacrylonitrile pole piece, diaphragm and lithium metal sheet are assembled into a button battery in sequence, and a self-healing polymer electrolyte precursor solution is injected on both sides of the diaphragm for in-situ thermal polymerization to obtain a solid-state lithium-sulfur battery.
[0015] Further, the molecular weight of polyacrylonitrile is 150,000-600,000; the particle size is 50-80 μm;
[0016] The speed of the sand mill used for sand grinding is 1000-2500rpm, and the running time is 1-5h;
[0017] The spray drying conditions are: the spray drying inlet temperature is 180-230℃, the liquid inlet rate is 5-30mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa and the atomization pressure is 0.25Mpa.
[0018] Furthermore, the first heat treatment conditions are: temperature 280-450°C, heating rate 2-5°C / min, and holding time 2-8h; the second heat treatment conditions are: temperature 180-220°C / min, heating rate 5°C / min, and holding time 12h-24h;
[0019] The catalyst is at least one of selenium, iodine, silicon, boron and phosphorus;
[0020] The mass ratio of sublimated sulfur to polyacrylonitrile particles is 1-10:1, and the amount of the catalyst used accounts for 2wt%-10wt% of the mass of the polyacrylonitrile particles.
[0021] Furthermore, the electric carbon black is at least one of Super P, Super C45, Super C60, carbon nanotube slurry and Ketjen black;
[0022] The binder is at least one of sodium carboxymethyl cellulose, LA132, LA133 and sodium alginate;
[0023] The mass ratio of the sulphurized polyacrylonitrile positive electrode, conductive carbon black and binder is 7:2:1;
[0024] The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide;
[0025] The concentration of lithium salt in the basic electrolyte precursor is 1-3 mol / L;
[0026] The amount of polymer monomer used is 2wt%-20wt% of the mass of the basic electrolyte precursor; the amount of self-healing functional monomer used is 1wt%-10wt% of the mass of the basic electrolyte precursor; the amount of ionic liquid used is 5wt%-50wt% of the mass of the basic electrolyte precursor; the amount of thermal initiator used is 0.1wt%-2wt% of the mass of the basic electrolyte precursor.
[0027] Further, the polymer monomer is one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,3-butylene glycol diacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate;
[0028] The ionic liquid is one of bis(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, N-methyl-N,N-diethyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide, N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpyrrole bis(trifluoromethylsulfonyl)imide;
[0029] The thermal initiator is one of azobisisobutyronitrile, methylenebisacrylamide and benzoyl peroxide;
[0030] The structure of the self-healing functional monomer is an embedded polymer containing 2-ureido-4[1H]-pyrimidinone ethyl methacrylate with multiple hydrogen bonds, polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment.
[0031] Furthermore, the structural formula of 2-ureido-4[1H]-pyrimidinone ethyl methacrylate containing multiple hydrogen bonds is:
[0032]
[0033] Further, the structural formula of the embedded polymer containing polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment is:
[0034]
[0035] Furthermore, the temperature of the in-situ thermal polymerization is 50°C-100°C, and the time is 15-720 min.
[0036] Furthermore, the diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm, GF / C glass fiber diaphragm, cellulose diaphragm and polyimide diaphragm.
[0037] A solid-state lithium-sulfur battery.
[0038] Further, the synthesis steps of 2-ureido-4[1H]-pyrimidinone ethyl methacrylate containing multiple hydrogen bonds are:
[0039] (1) Add 1 g of 6-methylisocytosine to 30 mL of dimethyl sulfoxide and stir at 150°C for 10 min. Then cool the solution to ambient temperature.
[0040] (2) 1.98 g of 2-isocyanatoethyl methacrylate was added to the flask, and a white solid was precipitated when the mixture was cooled in an ice bath. Then, the precipitate was collected and washed three times with methanol, and the precipitate was vacuum dried at 40° C. for 12 h, and the resulting white powder was collected.
[0041] Further, the synthesis steps of the embedded polymer containing polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment are:
[0042] (1) Polytetramethylene ether glycol (PTMEG) (14.5 g) was added to a three-necked reactor equipped with a mechanical stirrer, and then heated in an oil bath at 100° C. for 1 h under vacuum, and then cooled to 70° C.
[0043] (2) Isophorone diisocyanate IPDI (6.77 g) and dibutyltin dilaurate DBTDL (0.05 g) completely dissolved in dimethylacetamide (5 mL) were slowly added to the flask and stirred for 2 h under an argon atmosphere.
[0044] (3) Afterwards, bis(4-hydroxyphenyl) disulfide (3.63 g) dissolved in dimethylacetamide (10 mL) was directly added into the reactor as a chain extender, and then heated to 40° C. for 18 h.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] The present invention optimizes the preparation process of the existing lithium-sulfur battery sulfurized polyacrylonitrile positive electrode by introducing a catalyst into the sulfurized polyacrylonitrile positive electrode, uses the catalyst to accelerate the reaction kinetics, improves the lithium ion diffusion coefficient, realizes the transformation between the soluble short-chain intermediate product (Li2Sn, n≤4) and the insoluble product Li2S2 / Li2S, thereby effectively inhibiting the polysulfide shuttle effect, combining the advantages of the high electronic conductivity of the catalyst and the high specific capacity of sulfur, and improving the electrochemical performance of the sulfurized polyacrylonitrile; the technical solution provided by the present invention obtains a self-healing polymer electrolyte through an in-situ polymerization strategy, which greatly improves the solid-solid contact interface compatibility between the electrode electrolyte and the traditional polymer electrolyte, reduces the interface contact resistance, and obtains a polymer electrolyte with high ionic conductivity, high safety and good interface compatibility; the present invention provides a gel polymer solid electrolyte with self-healing ability by introducing a self-healing functional monomer, reduces the interface resistance and improves the performance of the solid-state lithium-sulfur battery. Due to its dynamic covalent disulfide bonds and hydrogen bonds, the proposed self-healing polymer electrolyte exhibits rapid interface healing ability, realizes dynamic optimization and regulation of the electrode electrolyte interface, and has application value in flexible electronic devices; the solid-state lithium-sulfur battery of the present invention using sulfurized polyacrylonitrile positive electrode and self-healing polymer electrolyte has a simple preparation process, matches the existing commercial production line, and can be conveniently and low-costly prepared solid-state lithium-sulfur batteries. After electrochemical testing, it shows good cycle performance and rate performance and safety, while achieving high energy density and high safety. The present invention effectively inhibits the dissolution of polysulfides and avoids the shuttle effect. The self-healing polymer electrolyte prepared in situ improves the solid-solid interface contact compatibility and improves the capacity retention rate and safety of lithium-sulfur batteries.
[0047] Furthermore, the present invention processes the block polyacrylonitrile in the shape of large particles with an industrial-grade particle size of 50-80 μm by a sand mill, the rotation speed of the sand mill is 1000-2500 rpm, and the operation time is 1-5 hours; the granular material is ground to improve the stability and uniformity of the particles; the internal primary particles are exposed to the outside, so that elemental sulfur can more easily penetrate into the polyacrylonitrile sphere, the sulfur carrying capacity is improved, and the reaction is more sufficient; the spray drying process is a construction process from primary particles to secondary particles, and the pretreated polyacrylonitrile can replace homopolymerized polyacrylonitrile, solving the high cost problem of the positive electrode relying on homopolymerized sulfide polyacrylonitrile. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] Figure 1 A preparation flow chart of a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte provided by the present invention;
[0049] Figure 2The SEM images of the sulfurized polyacrylonitrile prepared using large-particle polypropylene in Comparative Example 1 and the composite sulfurized polyacrylonitrile prepared according to Example 1 of the present invention; wherein (a) is Comparative Example 1, and (b) is Example 1;
[0050] Figure 3 This is a rendering of the self-healing polymer electrolyte prepared according to Example 1 of the present invention;
[0051] Figure 4 This is a test result diagram of the self-healing polymer electrolyte prepared according to Example 1 of the present invention used in a lithium metal symmetric battery;
[0052] Figure 5 Capacity-voltage curves of the solid-state lithium-sulfur battery prepared according to Example 1 of the present invention at the 1st, 10th, 20th, 50th, 100th and 200th cycles;
[0053] Figure 6 This is a cycle performance diagram of a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte prepared according to Example 1 of the present invention.
[0054] Figure 7 This is a cycle performance diagram of the solid-state lithium-sulfur battery prepared according to Comparative Example 1 of the present invention.
[0055] Figure 8 This is a cycle performance diagram of the lithium-sulfur battery prepared according to Comparative Example 2 of the present invention.
[0056] Fig. 9 This is a cycle performance diagram of the solid-state lithium-sulfur battery prepared according to Comparative Example 3 of the present invention.
[0057] Fig.10 This is a diagram showing the self-healing test effect of the electrolyte prepared according to Comparative Example 4 of the present invention.
[0058] Fig.11 This is a cycle performance diagram of the solid-state lithium-sulfur battery prepared according to Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0059] In order to make the above-mentioned purpose, performance characteristics and preparation method of the present invention clearer and easier to understand, the present invention is further described in conjunction with the following examples. The examples are preferred in the experimental process and are only used to more completely illustrate the present invention, but cannot be understood as limiting the scope of application of the present invention.
[0060] In order to make the objectives, technical solutions and advantages of the embodiments of the present invention more obvious and easier to understand, the technical solutions in the embodiments of the present invention will be clearly described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0061] The instruments and pharmaceutical materials used in the present invention are all commercially available.
[0062] The present invention provides a method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, comprising the following steps:
[0063] (1) The polyacrylonitrile raw material to be ground is put into the mill together with an appropriate amount of water by a sand mill, and then finely ground by high-speed rotation in the cylinder to form a uniform slurry. Then, the spray drying technology is used to achieve rapid conversion and efficient production of the material, and obtain porous polyacrylonitrile particles with uniform size and regular shape; the sulfur carrying capacity is increased, and the conductivity and mechanical stability of the particles are improved.
[0064] (2) the polyacrylonitrile particles obtained in step (1) are uniformly mixed with sublimated sulfur and a catalyst by ball milling, wherein the catalyst significantly improves the reaction kinetics of the sulfur positive electrode and accelerates the diffusion and transmission of lithium ions, and the mixture is heat treated in an argon atmosphere to obtain a uniformly mixed light yellow powder, and then the mixture is subjected to a first stage of heat treatment in a tubular furnace in an argon atmosphere, and then naturally cooled to room temperature, and then the tubular furnace is heated to perform a second stage of heat treatment, and then naturally cooled to room temperature to prepare a sulfurized polyacrylonitrile positive electrode powder;
[0065] (3) The polyacrylonitrile sulfide positive electrode in the above step (2) is mixed with the conductive carbon black and the binder in a mass ratio of 7:2:1, coated on one side of the carbon-coated aluminum foil, and dried to obtain the polyacrylonitrile sulfide electrode;
[0066] (4) mixing ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate in equal volumes, then adding lithium salt to the mixed solution, stirring magnetically to obtain a basic electrolyte precursor, then adding polymer monomers, self-healing functional monomers, ionic liquids, and thermal initiators, and stirring thoroughly to obtain a self-healing polymer electrolyte precursor solution;
[0067] (5) Assembling a button cell in sequence using the polyacrylonitrile sulfide electrode, diaphragm, and lithium metal sheet in the above step (3), injecting the self-healing polymer electrolyte precursor solution in the above step (4) on both sides of the diaphragm, completing the assembly and performing in-situ thermal polymerization to obtain a self-healing polymer electrolyte, and then obtaining a solid-state lithium-sulfur battery using a polyacrylonitrile sulfide positive electrode and a self-healing polymer electrolyte.
[0068] In step (1), the speed of the sand mill is 1000-2500 rpm, and the operation time is 1-5 h; the inlet temperature of the spray drying is 180-230 ° C, and the liquid inlet rate is 5-30 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa and the atomization pressure is 0.25Mpa.
[0069] The molecular weight of the polyacrylonitrile in step (1) is 150,000-600,000; the particle size is 50-80 μm;
[0070] The catalyst in step (2) includes at least one of selenium, iodine, silicon, boron and phosphorus; the mass ratio of sublimated sulfur to polyacrylonitrile is 1-10:1, and the mass ratio of catalyst to polyacrylonitrile is 2wt%-10wt%. The ball milling time is 6-12h. The first stage heat treatment condition is 280-450℃, the heating rate is 2-5℃ / min, and the heat preservation time is 2-8h; the second stage heat treatment condition is 180-220℃ / min, the heating rate is 5℃ / min, and the heat preservation time is 12h-24h.
[0071] In step (3), the conductive carbon black is at least one of Super P, Super C45, Super C60, carbon nanotube slurry and Ketjen black; the aqueous binder is at least one of sodium carboxymethyl cellulose, LA132, LA133 and sodium alginate;
[0072] The lithium salt in step (4) is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorooxalate borohydride, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide, the concentration of the lithium salt in the solution is 1-3 mol / L, the magnetic stirring temperature is room temperature, and the stirring time is 0.5h-12h;
[0073] In step (4), the polymer monomer accounts for 2wt%-20wt% of the basic electrolyte precursor; the self-healing functional monomer accounts for 1wt%-10wt% of the basic electrolyte precursor; the ionic liquid accounts for 5wt%-50wt% of the basic electrolyte precursor; the thermal initiator accounts for 0.1wt%-2wt% of the basic electrolyte precursor;
[0074] The polymer monomer in step (4) is one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,3-butylene glycol diacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate;
[0075] Preferably, the ionic liquid is one of bis(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, N-methyl-N,N-diethyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide, N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpyrrole bis(trifluoromethylsulfonyl)imide;
[0076] Preferably, the thermal initiator is one of azobisisobutyronitrile, methylenebisacrylamide and benzoyl peroxide;
[0077] Furthermore, the solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte is characterized in that the structure of the self-healing functional monomer in step (4) is 2-ureido-4[1H]-pyrimidinone ethyl methacrylate (UPyMA) containing multiple hydrogen bonds, and a molten polymer (PTMEG-HDI-BHDS) containing polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment.
[0078]
[0079] Preferably, the synthesis steps of the self-healing functional monomer UPyMA are:
[0080] (1) Add 1 g of 6-methylisocytosine to 30 mL of dimethyl sulfoxide and stir at 150°C for 10 min. Then cool the solution to ambient temperature.
[0081] (2) 1.98 g of 2-isocyanatoethyl methacrylate was added to the flask, and a white solid was precipitated when the mixture was cooled in an ice bath. Then, the precipitate was collected and washed three times with methanol, and the precipitate was vacuum dried at 40° C. for 12 h, and the resulting white powder was collected.
[0082] Preferably, the synthesis steps of the self-healing functional monomer PTMEG-HDI-BHDS are:
[0083] (1) Polytetramethylene ether glycol (PTMEG) (14.5 g) was added to a three-necked reactor equipped with a mechanical stirrer, and then heated in an oil bath at 100° C. for 1 h under vacuum, and then cooled to 70° C.
[0084] (2) Isophorone diisocyanate IPDI (6.77 g) and dibutyltin dilaurate DBTDL (0.05 g) completely dissolved in dimethylacetamide (5 mL) were slowly added to the flask and stirred for 2 h under an argon atmosphere.
[0085] (3) Afterwards, bis(4-hydroxyphenyl) disulfide (3.63 g) dissolved in dimethylacetamide (10 mL) was directly added into the reactor as a chain extender, and then heated to 40° C. for 18 h.
[0086] The temperature of the thermal polymerization in step (5) is 50°C-100°C, and the holding time is 15-720min; the diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm, GF / C glass fiber diaphragm, cellulose diaphragm and polyimide diaphragm.
[0087] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte is obtained by using the above-mentioned preparation method.
[0088] The scheme of the present invention is described in more detail below with reference to the embodiments.
[0089] Example 1
[0090] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0091] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 150,000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 1000 rpm for 4 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain a nano-scale polyacrylonitrile material. The spray drying conditions were an inlet temperature of 200 °C and a liquid inlet rate of 10 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0092] (2) Sublimed sulfur, pretreated polyacrylonitrile and selenium powder were mixed in a mass ratio of 4:1:0.08, anhydrous ethanol was added as a dispersant, ball milled for 12 hours, and dried to obtain a uniform light yellow mixture. The light yellow mixture was then placed in an alumina porcelain boat in an argon atmosphere and heated to 350°C at a heating rate of 5°C / min for 6 hours, cooled naturally to room temperature, and then heated to 200°C at a rate of 5°C / min for 24 hours, and excess sulfur that did not participate in the reaction was removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0093] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2): Super P: sodium carboxymethyl cellulose = 7:2:1 are mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, i.e., the composite vulcanized polyacrylonitrile electrode sheet;
[0094] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium bis(trifluoromethylsulfonyl)imide is added to the mixed solution, and magnetic stirring is performed at room temperature for 1 hour to obtain a basic electrolyte precursor, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide in the basic electrolyte precursor is 1 mol / L, and then 5 wt% of ethoxylated trimethylolpropane triacrylate, 2 wt% of self-healing functional monomer UPyMA, 10 wt% of di(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, and 0.2 wt% of azobisisobutyronitrile are added, and magnetic stirring is performed at room temperature for 2 hours to obtain a self-healing polymer electrolyte precursor solution;
[0095] (5) The composite vulcanized polyacrylonitrile electrode, glass fiber separator GF / A, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the separator. The assembly is completed and stored in an oven at 70°C for 60 minutes to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0096] Example 2
[0097] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0098] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 600000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 2000 rpm for 3 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain nano-scale polyacrylonitrile material. The conditions for spray drying were an inlet temperature of 220 °C and a liquid inlet rate of 30 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0099] (2) Sublimed sulfur, pretreated polyacrylonitrile and selenium powder were mixed in a mass ratio of 8:1:0.04, anhydrous ethanol was added as a dispersant, ball milled for 6 hours, and dried to obtain a uniform light yellow mixture. The light yellow mixture was then placed in an alumina porcelain boat in an argon atmosphere tube furnace and heated to 450°C at a heating rate of 3°C / min for 450 minutes, cooled naturally to room temperature, and then heated to 180°C at a rate of 5°C / min for 20 hours, and the excess sulfur that did not participate in the reaction was removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0100] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2) is mixed evenly with Super C45 and LA133 in a mass ratio of 7:2:1, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, namely the composite vulcanized polyacrylonitrile electrode sheet;
[0101] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium bis(difluorosulfonyl)imide is added to the mixed solution, and magnetic stirring is performed at room temperature for 2 hours to obtain a basic electrolyte precursor, wherein the concentration of lithium bis(difluorosulfonyl)imide in the basic electrolyte precursor is 1.2 mol / L, and then 3 wt% of pentaerythritol tetraacrylate, 1 wt% of self-healing functional monomer PTMEG-HDI-BHDS, 10 wt% of N-methyl-N-propylpyrrole di(trifluoromethylsulfonyl)imide, and 0.2 wt% of azobisisobutyronitrile are added based on the weight of the basic electrolyte precursor, and magnetic stirring is performed at room temperature for 2 hours to obtain a self-healing polymer electrolyte precursor solution;
[0102] (5) The composite vulcanized polyacrylonitrile electrode, PP2500, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the diaphragm to complete the assembly and store in a 60°C oven for 720 min to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0103] Example 3
[0104] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0105] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 250,000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 2100 rpm for 2 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain a nano-scale polyacrylonitrile material. The conditions for spray drying were an inlet temperature of 180 °C and a liquid inlet rate of 30 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0106] (2) Sublimed sulfur, pretreated polyacrylonitrile and phosphorus powder are mixed in a mass ratio of 6:1:0.06, anhydrous ethanol is added as a dispersant, ball milled for 300 minutes, and dried to obtain a uniform light yellow mixture. The light yellow mixture is then placed in an alumina porcelain boat in an argon atmosphere and heated to 330°C at a heating rate of 5°C / min for 480 minutes, cooled naturally to room temperature, and then heated to 220°C at a rate of 5°C / min for 24 hours, and excess sulfur that has not participated in the reaction is removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0107] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2): Ketjen black: sodium alginate = 7:2:1 by mass ratio are mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, namely the composite vulcanized polyacrylonitrile electrode sheet;
[0108] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium difluoroborate is added to the mixed solution, and magnetic stirring is performed at room temperature for 1 hour to obtain a basic electrolyte precursor, wherein the concentration of lithium difluoroborate in the basic electrolyte precursor is 2 mol / L, and then 10 wt% of polyethylene glycol diacrylate, 5 wt% of self-healing functional monomer UPyMA, 30 wt% of N-methyl-N, N-diethyl-N-(2-methoxyethyl) ammonium di(trifluoromethylsulfonyl)imide, and 1 wt% of methylenebisacrylamide are added based on the weight of the basic electrolyte precursor, and magnetic stirring is performed at room temperature for 3 hours to obtain a self-healing polymer electrolyte precursor solution;
[0109] (5) The composite vulcanized polyacrylonitrile electrode, polyimide diaphragm, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the diaphragm. The assembly is completed and stored in a 90° C. oven for 120 min to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0110] Example 4
[0111] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0112] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 250,000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 1500 rpm for 5 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain a nano-scale polyacrylonitrile material. The conditions for spray drying were an inlet temperature of 190 °C and a liquid inlet rate of 25 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0113] (2) Sublimed sulfur, pretreated polyacrylonitrile and iodine powder are mixed in a mass ratio of 4:1:0.02, anhydrous ethanol is added as a dispersant, ball milled for 12 hours, and dried to obtain a uniform light yellow mixture. The light yellow mixture is then placed in an alumina porcelain boat in an argon atmosphere and heated to 300°C at a heating rate of 5°C / min for 8 hours, cooled naturally to room temperature, and then heated to 210°C at a rate of 5°C / min for 12 hours, and excess sulfur that has not participated in the reaction is removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0114] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2) is mixed evenly with Super C65 and LA132 in a mass ratio of 7:2:1, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, namely the composite vulcanized polyacrylonitrile electrode sheet;
[0115] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium hexafluorophosphate is added to the mixed solution, and magnetic stirring is performed at room temperature for 1 hour to obtain a basic electrolyte precursor, wherein the concentration of lithium hexafluorophosphate in the basic electrolyte precursor is 1 mol / L, and then 3 wt% of pentaerythritol tetraacrylate, 10 wt% of self-healing functional monomer UPyMA, 30 wt% of di(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, and 0.2 wt% of benzoyl peroxide are added, and magnetic stirring is performed at room temperature for 1 hour to obtain a self-healing polymer electrolyte precursor solution;
[0116] (5) The composite vulcanized polyacrylonitrile electrode, cellulose diaphragm, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the diaphragm to complete the assembly and store in an oven at 80°C for 300 min to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0117] Example 5
[0118] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0119] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 150,000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 1700 rpm for 1 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain nano-scale polyacrylonitrile material. The conditions for spray drying were an inlet temperature of 190 °C and a liquid inlet rate of 15 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0120] (2) Sublimed sulfur, pretreated polyacrylonitrile and silicon powder are mixed in a mass ratio of 8:1:0.04, anhydrous ethanol is added as a dispersant, ball milled for 8 hours, and dried to obtain a uniform light yellow mixture. The light yellow mixture is then placed in an alumina porcelain boat in an argon atmosphere and heated to 430°C at a heating rate of 5°C / min for 5 hours, cooled naturally to room temperature, and then heated to 200°C at a rate of 5°C / min for 12 hours, excess sulfur that has not participated in the reaction is removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0121] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2): carbon nanotube slurry: sodium carboxymethyl cellulose = 7:2:1 mass ratio is mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, namely the composite vulcanized polyacrylonitrile electrode sheet;
[0122] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium bis(trifluoromethylsulfonyl)imide is added to the mixed solution, and magnetic stirring is performed at room temperature for 4 hours to obtain a basic electrolyte precursor, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide in the basic electrolyte precursor is 1.5 mol / L, and then 15 wt% of tripropylene glycol diacrylate, 8 wt% of self-healing functional monomer UPyMA, 40 wt% of di(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, and 2 wt% of azobisisobutyronitrile are added based on the weight of the basic electrolyte precursor, and magnetic stirring is performed at room temperature for 2 hours to obtain a self-healing polymer electrolyte precursor solution;
[0123] (5) The composite vulcanized polyacrylonitrile electrode, cellulose diaphragm, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the diaphragm. The assembly is completed and stored in an oven at 100° C. for 20 min to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0124] Example 6
[0125] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0126] (1) 10 g of large-particle polyacrylonitrile (relative molecular weight 150,000) with a particle size of 50-80 μm was dispersed in water and processed in a sand mill at a speed of 2500 rpm for 1 h. The solution was then ultrasonically dispersed to obtain a uniform mixture, and the slurry obtained by spray drying was prepared to obtain a nano-scale polyacrylonitrile material. The conditions for spray drying were an inlet temperature of 230 °C and a liquid inlet rate of 5 mL min -1 , carrier gas rate was 40 mL min -1 , the needle pressure is 0.2Mpa, the atomization pressure is 0.25Mpa, and the pretreated polyacrylonitrile powder is obtained after drying;
[0127] (2) Sublimed sulfur, pretreated polyacrylonitrile and boron powder were mixed in a mass ratio of 8:1:0.1, anhydrous ethanol was added as a dispersant, ball milled for 10 hours, and dried to obtain a uniform light yellow mixture. The light yellow mixture was then placed in an alumina porcelain boat in an argon atmosphere and heated to 280°C at a heating rate of 2°C / min for 2 hours, cooled naturally to room temperature, and then heated to 190°C at a rate of 5°C / min for 15 hours, and excess sulfur that did not participate in the reaction was removed, and cooled naturally to room temperature to prepare a composite sulfurized polyacrylonitrile;
[0128] (3) The composite vulcanized polyacrylonitrile positive electrode prepared in the above step (2): Super C60: sodium carboxymethyl cellulose = 7:2:1 are mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried using a slicer to prepare a positive electrode sheet with a diameter of 15 mm, namely the composite vulcanized polyacrylonitrile electrode sheet;
[0129] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then lithium tetrafluoroborate and lithium bis(difluorosulfonyl)imide are added to the mixed solution, and magnetic stirring is performed at room temperature for 12 hours to obtain a basic electrolyte precursor, wherein the concentration of lithium tetrafluoroborate in the basic electrolyte precursor is 1 mol / L, and the concentration of lithium bis(difluorosulfonyl)imide is 2 mol / L, and then 2 wt% of poly(ethylene glycol) dimethacrylate, 5 wt% of self-healing functional monomer UPyMA, 1.5 wt% of N-methyl-N-propylpiperidinium di(trifluoromethylsulfonyl)imide, and 0.5 wt% of methylenebisacrylamide are added, and magnetic stirring is performed at room temperature for 12 hours to obtain a self-healing polymer electrolyte precursor solution;
[0130] (5) The composite vulcanized polyacrylonitrile electrode, cellulose diaphragm, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, and 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the diaphragm. The assembly is completed and stored in an oven at 100° C. for 20 min to complete thermal polymerization, thereby preparing a solid-state lithium-sulfur battery using a vulcanized polyacrylonitrile positive electrode and a self-healing polymer electrolyte.
[0131] Comparative Example 1
[0132] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0133] (1) No pretreatment of large-particle polyacrylonitrile raw materials with a size of 50-80 μm;
[0134] (2) according to the preparation method of Example 1;
[0135] (3) according to the preparation method of Example 1;
[0136] (4) according to the preparation method of Example 1;
[0137] (5) according to the preparation method of Example 1;
[0138] The difference between Comparative Example 1 and Example 1 is that in step (1), the spherical large-particle polypropylene raw material is not processed by sand milling and spray drying process, but is directly ball-milled with sublimated sulfur and catalyst. The sulfur content of the obtained polyacrylonitrile material is low and the discharge specific capacity is low. Figure 7 .
[0139] Comparative Example 2
[0140] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0141] (1) according to the preparation method of Example 1;
[0142] (2) according to the preparation method of Example 1;
[0143] (3) according to the preparation method of Example 1;
[0144] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then 1 mol / L lithium bis(trifluoromethylsulfonyl)imide is added to the mixed solution, and magnetic stirring is performed at room temperature for 1 hour to obtain a basic electrolyte precursor, followed by adding 2 wt% of a self-healing functional monomer UPyMA and 10 wt% of di(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, and magnetic stirring is performed at room temperature for 2 hours to obtain a self-healing electrolyte precursor solution;
[0145] (5) The assembly procedure of the lithium-sulfur button cell is the same as that of Example 1.
[0146] The difference between Comparative Example 2 and Example 1 is that no polymer monomer and polymerization initiator are added in step (4), and a liquid electrolyte is used when assembling the battery, which belongs to a liquid lithium-sulfur battery. The capacity of the liquid lithium-sulfur battery in this comparative example decays significantly after 200 cycles, see Figure 8 .
[0147] Comparative Example 3
[0148] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0149] (1) according to the preparation method of Example 1;
[0150] (2) No selenium powder was added as a catalyst, and the rest was the same as the preparation method of Example 1;
[0151] (3) according to the preparation method of Example 1;
[0152] (4) according to the preparation method of Example 1;
[0153] (5) According to the preparation method of Example 1.
[0154] The difference between Comparative Example 3 and Example 1 is that no catalyst selenium powder is added when preparing the sulfide polyacrylonitrile in step (2), resulting in poor battery cycle performance and low discharge capacity. Fig. 9 .
[0155] Comparative Example 4
[0156] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0157] (1) according to the preparation method of Example 1;
[0158] (2) according to the preparation method of Example 1;
[0159] (3) according to the preparation method of Example 1;
[0160] (4) Ethylene carbonate, dimethyl carbonate, and fluoroethylene carbonate are mixed in a volume ratio of 1:1:1, and then 1 mol / L lithium bis(trifluoromethylsulfonyl)imide is added to the mixed solution, and magnetic stirring is performed at room temperature for 1 hour to obtain a basic electrolyte precursor, followed by adding 5 wt% ethoxylated trimethylolpropane triacrylate, 10 wt% di(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, and 0.2 wt% azobisisobutyronitrile, and magnetic stirring is performed at room temperature for 2 hours to obtain a self-healing polymer electrolyte precursor solution;
[0161] (5) According to the preparation method of Example 1.
[0162] The difference between Comparative Example 4 and Example 1 is that in step (4), the self-healing polymer electrolyte precursor solution is prepared without adding 2 wt% of the self-healing functional monomer UPyMA, resulting in poor interface contact and the electrolyte cannot self-heal after being damaged by external force. Fig.10 .
[0163] Comparative Example 5
[0164] A solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, wherein the preparation method comprises the following steps:
[0165] (1) according to the preparation method of Example 1;
[0166] (2) according to the preparation method of Example 1;
[0167] (3) according to the preparation method of Example 1;
[0168] (4) according to the preparation method of Example 1;
[0169] (5) The composite vulcanized polyacrylonitrile pole piece, glass fiber separator GF / A, and lithium metal sheet in the above step (3) are assembled into a button battery in sequence, 30 μL of the self-healing polymer electrolyte precursor solution in the above step (4) is added to both sides of the separator, and the battery is kept on a hot plate at 70°C for 60 minutes to complete thermal polymerization, and then a button battery sealing machine is used to complete the battery assembly.
[0170] The difference between Comparative Example 5 and Example 1 is that the polymerization method used in step (5) is non-in-situ polymerization, which leads to a large impedance of the solid-state battery and poor wettability of the diaphragm, and the capacity of the sulfide polyacrylonitrile material cannot be brought into play. Fig.11 .
[0171] Figure 2 (a) and (b) are SEM images of the composite sulfurized polyacrylonitrile prepared in Comparative Example 1 and Example 1 of the present invention; it can be seen that the particle size of the composite sulfurized polyacrylonitrile obtained in Example 1 is 2-10 μm, and the distribution is more uniform.
[0172] Figure 3 This is a rendering of the self-healing polymer electrolyte prepared according to Example 1 of the present invention. It can be seen that the gel polymer electrolyte can be restored to its initial state after being cut by external force and then left to heal for 60 minutes.
[0173] Figure 4 The test results of the self-healing polymer electrolyte prepared according to Example 1 of the present invention for lithium metal symmetric batteries are shown in Figure 1. -2 The lower symmetric lithium-ion battery maintains a stable overpotential during the 200 h cycle.
[0174] Figure 5 The capacity-voltage curves of the 1st, 10th, 20th, 50th and 100th cycles of the solid-state lithium-sulfur battery prepared according to Example 1 of the present invention show that the capacity remains stable with almost no attenuation during the cycle.
[0175] Figure 6 The cycle performance diagram of the solid-state lithium-sulfur battery using sulfurized polyacrylonitrile positive electrode and self-healing polymer electrolyte prepared according to Example 1 of the present invention shows that 99% of the discharge capacity and 99.9% of the coulombic efficiency can be maintained after 260 cycles at a rate of 0.5C.
[0176] Figure 7 This is a performance diagram of a solid-state lithium-sulfur battery prepared according to Comparative Example 1 of the present invention. Since the large-particle polyacrylonitrile is not processed, the sulfur content in the composite material is low and the battery specific capacity is low.
[0177] Figure 8 This is a performance diagram of a lithium-sulfur battery prepared according to Comparative Example 2 of the present invention, which is a liquid battery. The shuttle effect of polysulfides occurs during the cycle, resulting in a decrease in battery capacity.
[0178] Fig. 9 This is a performance diagram of a lithium-sulfur battery prepared according to Comparative Example 3 of the present invention. Since no catalyst is added, the electrochemical reaction kinetics are poor and the discharge specific capacity of the battery is significantly lower than that of Example 1.
[0179] Fig.10 This is a self-healing test effect diagram of the electrolyte prepared according to Comparative Example 4 of the present invention. It can be seen that the gel polymer electrolyte cannot recover the cracks after being cut by external force and left to heal for 60 minutes.
[0180] Fig.11 The performance diagram of the lithium-sulfur battery prepared according to Comparative Example 5 of the present invention shows that the discharge capacity of the solid-state battery is only 550 mAh g due to poor interface contact. -1 .
[0181] The above embodiments are only embodiments with better effects in the present invention and cannot be understood as limiting the present invention. Any person skilled in the art can change, modify or replace the above methods without changing the technical solution and essence of the present invention.
Claims
1. A method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte, characterized in that: The following steps are involved: The polyacrylonitrile is subjected to sand milling and then granulated by spray drying to obtain porous polyacrylonitrile particles; The porous polyacrylonitrile particles, sublimated sulfur and a catalyst are ball-milled to obtain a powder, and the powder is subjected to a first heat treatment and then to a second heat treatment to obtain a sulfurized polyacrylonitrile positive electrode powder; The polyacrylonitrile sulfide positive electrode powder, conductive carbon black and binder are mixed evenly, coated on one side of the carbon-coated aluminum foil, and dried to obtain the polyacrylonitrile sulfide electrode sheet; Adding lithium salt to a mixed solution of ethylene carbonate, dimethyl carbonate and fluoroethylene carbonate, stirring, to obtain a basic electrolyte precursor; Adding polymer monomers, self-healing functional monomers, ionic liquids and thermal initiators to a basic electrolyte precursor, stirring, and obtaining a self-healing polymer electrolyte precursor solution; The sulfide polyacrylonitrile pole piece, diaphragm and lithium metal sheet are assembled into a button battery in sequence, and a self-healing polymer electrolyte precursor solution is injected on both sides of the diaphragm for in-situ thermal polymerization to obtain a solid-state lithium-sulfur battery.
2. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The molecular weight of polyacrylonitrile is 150,000-600,000, and the particle size is 50-80 μm; The speed of the sand mill used for sand grinding is 1000-2500rpm, and the running time is 1-5h; The spray drying conditions are: the spray drying inlet temperature is 180-230℃, the liquid inlet rate is 5-30mL min -1 , carrier gas rate is 40 mL min -1 , the needle pressure is 0.2Mpa and the atomization pressure is 0.25Mpa.
3. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The first stage heat treatment conditions are: temperature 280-450℃, heating rate 2-5℃ / min, holding time 2-8h; the second stage heat treatment conditions are: temperature 180-220℃ / min, heating rate 5℃ / min, holding time 12h-24h; The catalyst is at least one of selenium, iodine, silicon, boron and phosphorus; The mass ratio of sublimated sulfur to polyacrylonitrile particles is 1-10:1, and the amount of the catalyst used accounts for 2wt%-10wt% of the mass of the polyacrylonitrile particles.
4. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The conductive carbon black is at least one of Super P, Super C45, Super C60, carbon nanotube slurry and Ketjen black; The binder is at least one of sodium carboxymethyl cellulose, LA132, LA133 and sodium alginate; The mass ratio of the sulphurized polyacrylonitrile positive electrode, conductive carbon black and binder is 7:2:1; The lithium salt is at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluoroborate, lithium trifluoromethanesulfonate and lithium bis(difluorosulfonyl)imide; The concentration of lithium salt in the basic electrolyte precursor is 1-3 mol / L; The amount of the polymer monomer is 2wt%-20wt% of the mass of the basic electrolyte precursor; The amount of the self-healing functional monomer is 1wt%-10wt% of the mass of the basic electrolyte precursor; The amount of the ionic liquid used is 5wt%-50wt% of the mass of the basic electrolyte precursor; the amount of the thermal initiator used is 0.1wt%-2wt% of the mass of the basic electrolyte precursor.
5. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The polymer monomer is one of tetraethylene glycol diacrylate, polyethylene glycol diacrylate, dimethacrylate, tripropylene glycol diacrylate, ethylene glycol dimethacrylate, poly(ethylene glycol) dimethacrylate, 1,3-butylene glycol diacrylate, trimethylolpropane trimethacrylate, ethoxylated trimethylolpropane triacrylate and pentaerythritol tetraacrylate; The ionic liquid is one of bis(trifluoromethylsulfonyl)1-ethyl-3-methylimidazole, N-methyl-N,N-diethyl-N-(2-methoxyethyl)ammonium bis(trifluoromethylsulfonyl)imide, N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpyrrole bis(trifluoromethylsulfonyl)imide; The thermal initiator is one of azobisisobutyronitrile, methylenebisacrylamide and benzoyl peroxide; The structure of the self-healing functional monomer is an embedded polymer containing 2-ureido-4[1H]-pyrimidinone ethyl methacrylate with multiple hydrogen bonds, polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment.
6. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 5, characterized in that: The structural formula of 2-ureido-4[1H]-pyrimidinone ethyl methacrylate containing multiple hydrogen bonds is:
7. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 5, characterized in that: The structural formula of the embedded polymer containing polytetramethylene ether glycol as a soft segment and isophorone diisocyanate / bis(4-hydroxyphenyl) disulfide as a hard segment is:
8. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The temperature of the in-situ thermal polymerization is 50°C-100°C, and the time is 15-720 minutes.
9. The method for preparing a solid-state lithium-sulfur battery using a sulfurized polyacrylonitrile positive electrode and a self-healing polymer electrolyte according to claim 1, characterized in that: The diaphragm is one of PP2500 type, PP2325 type, GF / A glass fiber diaphragm, GF / C glass fiber diaphragm, cellulose diaphragm and polyimide diaphragm.
10. A solid-state lithium-sulfur battery prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of Se-doped sulfurized polyacrylonitrile material
CN112759874A
Self-healing polymer-bonded explosive and preparation method thereof
CN115819159A
Battery based on sulfurized polyacrylonitrile positive electrode and gel electrolyte as well as preparation method and application of battery
CN115863775A
Method for preparing self-healing gel polymer electrolyte through in-situ polymerization
CN119119380A